Lessons From a New Continuing Education Mandate: The Experience of NASW-NYC. Issue 4 (7th August 2016) - Schachter, Robert
ABSTRACT: The New York City Chapter of the National Association of Social Workers (NASW-NYC), one of the largest in the country, launched a continuing education initiative in 2015 in response to passage of a new statute mandating that all MSW-level state licensed social workers begin accumulating approved hours of continuing education as a requirement for triennial licensure renewal. This article presents the NASW-NYC Chapter's response, along with the results of a participant evaluation of the conference launched by NASW-NYC to meet this new professional need.